ASPIRE Model for Academic Writing (Slideshow) - Chuah, Kee-Man (Universiti Malaysia Sarawak (UNIMAS), 2014)
Writing academic essays can be rather difficult as it requires some necessary "skills" in ensuring a piece of work remains "academic".